Assessment of consumers' confidence on Halal labelled manufactured food in Malaysia - Rezai, Golnaz; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir (Universiti Putra Malaysia Press, 2012)
Consumers' confidence in Halal labelled food is shaped by numerous factors. These include advertising, information on food ingredients and announcements, various Halal claims, and warnings on non Halal food products which carry a Halal logo. A survey was conducted among 1560 Muslim respondents all over Malaysia via a structured questionnaire to evaluate and assess consumers' degree of confidence in manufactured Halal labelled food products and the Halal logo that comes with them. A descriptive statistic was used to identify the socio-economic/demographic characteristics and confidence of the respondents toward the Halal labelled food. The logit model was used to determine the extent to which selected socio-economic/demographic characteristics and attitudinal factors influenced the respondents' opinions towards and confidence in Halal labelled food products. In general, various socio-economic/demographic and attitudinal characteristics were found to significantly influence the likelihood of the respondents' degree of confidence in the "halalness" of manufactured food products that carry the Halal logo. The older generation, particularly the rural folk, and those with higher education level and higher level of religiosity seemed to be likely less confident with the Halal labelled food products. Meanwhile, attitudinal factors such as without JAKIM Halal logo, food products from non-Muslim countries, unfamiliar brand and no clear list of ingredients make consumers feel less confident with the products. Thus, most Malaysians are still unsure or do not have the full confidence in the Halal labelled food products with regard to its "halalness". Thus, monitoring and enforcement of the Halal laws and regulations have to be carried out on a regular basis to build consumers' confidence towards these products.